Characterization and expression in Pichia pastoris of a raw starch degrading glucoamylase (GA2) derived from Aspergillus flavus NSH9 - Kazi Muhammad, Rezaul Karim; Ahmad, Husaini; Ngieng, Ngui Sing; Tasmia, Tanim; Fazia, Mohd Sinang; Hasnain, Hussain; Md Anowar, Hossain; Hairul Azman, Roslan (Elsevier Inc., 2019)
The Aspergillus flavus NSH9 gene, encoding a pH and thermostable glucoamylase with a starch binding domain (SBD), was expressed in Pichia pastoris to produce recombinant glucoamylase (rGA2). The full-length glucoamylase gene (2039 bp), and cDNA (1839 bp) encode a 612 amino acid protein most similar to glucoamylase from Aspergillus oryzae RIB40; the first 19 amino acids are presumed to be a signal peptide for secretion, and the SBD is at the C-terminal. The cDNA was successfully secreted by Pichia at 8.23 U mL-1, and the rGA2 was found to be: a 80 kDa monomer, stable from pH 3.0-9.0, with optimum catalytic activity at pH 5.0, active at temperatures up to 80°C (rGA2 retained 58% of its activity after 60 min of incubation at 70°C), and metal ions such as Na+, K+, Ca++ and Mg++ enhanced rGA2 enzyme activity. The starch degrading ability of rGA2 was also observed on raw sago starch and where prolonged incubation generated larger, deeper, holes on the starch granules, indicating rGA2 is an excellent candidate for industrial starch processing applications.